A new species-group of Macrostomus (Diptera, Empididae) with notable spotted wings recorded from the North Amazonia biogeographical component and a key to species-groups - Rafael, José Albertino; Vasconcelos, Manuela Santos (Zootaxa, 2024)
Two new species of Macrostomus Wiedemann are described, M. megatarsus sp. nov. from Brazil (Pará and Amapá) and French Guiana (Patawa and Régina) and M. polleti sp. nov. from Brazil (Amapá) and French Guiana (Mitaraka). Both species are treated in the new Macrostomus megatarsus species-group, which is defined based on male and female spotted wings, veins R2+3 and R4+5 sinuous leaving cell r2+3 that is subapically narrowed, and female legs with mid femur, hind femur, and hind tibia bearing dorsal and ventral pennate scales. A key to species is presented and the geographical distributions, restricted to the extreme east of the Amazon Basin in the North Amazonia biogeographical component, are mapped. Additionally, the first key to Macrostomus species-groups is presented.